Penerapan Model Green SCOR untuk Pengukuran Kinerja Green Supply Chain - Natalia, Christine; Astuario, Robertus (Metris: Jurnal Sains dan Teknologi, 2015)
Advances in science and technology that have an impact on the environment resulting in increasing human awareness of the condition of the environment, for example in the selection and use of environmentally friendly products. This requires businesses to apply the concept of environmental concerns in their business process, including the entire supply chain. Green supply chain management is a concept that integrates environmental thinking into supply chain management, which includes product design, procurement and selection of raw materials, manufacturing processes, delivery of final products to consumers, in addition reverse products used by consumers. This study aims to measure the performance of Green Supply Chain Management in the supply chain of a manufacturing industry. Performance measurement was conducted on the two main processes, namely the design of performance measurement model and weighting and scoring performance. This study uses a Green SCOR (Supply Chain Operations Reference) model to design the measurement model and AHP (Analytical Hierarchy Process) method to determine its weight. There are 16 KPIs (Key Performance Indicator) identified for use in performance measurement. Value performance indicators obtained for each aspect are as follows: Plan for 68, Source of 66.54, Make amounted to 58.89, Delivery of 32.80, and Return As much as 56.85. Referring to the model that is created, the value of the overall supply chain performance amounted at 60.13. Under the statutes of the company, the value is considered sufficient because it includes criteria for good performance, but it was on the threshold between good and bad categories. Continuous improvement in the supply chain by using a model Green SCOR will improve the company's performance, enhance corporate image and ultimately promote environmental sustainability for the future of mankind.